Answer:
![y(1) = 0.5518](https://img.qammunity.org/2021/formulas/mathematics/college/j2g624er4fdppdjhlibkwa0x1cr45inab5.png)
Explanation:
Given the differential equation
![e^(t) (dy)/(dt) +e^(t)y = t](https://img.qammunity.org/2021/formulas/mathematics/college/dx2ct2qmnpjx8zeffzcqmi9gu0sq2s80i1.png)
From the equation;
![e^(t) ((dy)/(dt) +y) = t\\(dy)/(dt) +y = (t)/(e^(t)) \\](https://img.qammunity.org/2021/formulas/mathematics/college/17b4wnbpgum8d6z2hzrrctk3mmavmookxn.png)
The resulting equation is a first order differential equation in the form
dy/dt + p(t)y = q(t)
The solution to the DE will be in the form yI =
where I is the integrating factor expressed as
![I = e^(\int\limits p(t) \, dt )](https://img.qammunity.org/2021/formulas/mathematics/college/6lgwn7lb9s8zvk6b6q4sar0y1947o2hsjh.png)
From the DE above p(t ) = 1 and q(t) =
![(t)/(e^(t) )](https://img.qammunity.org/2021/formulas/mathematics/college/kx1kt8n5pvt7mlfxql8dlndwwpu5dmx60p.png)
![I = e^(\int\limits1 \, dt )\\I = e^(t )\\](https://img.qammunity.org/2021/formulas/mathematics/college/ia2pa5ddw8dgqlotkdyezytqha6e1hnxnz.png)
The solution to the DE will become
![y e^(t ) = \int\limits e^(t ) *(t)/(e^(t ) ) \, dt\\y e^(t ) = \int\limits{t} \, dt \\y e^(t ) = (t^(2) )/(2) + C](https://img.qammunity.org/2021/formulas/mathematics/college/og9m6k50dbwd4ne8b8ssmlzj3ncfhugbqe.png)
If y(0) = 1 then;
![1 e^(0 ) = (0^(2) )/(2) + C\\1 = C](https://img.qammunity.org/2021/formulas/mathematics/college/w36gndnbm3vu071c7ebkqdan9698krho3j.png)
![y e^(t ) = (t^(2) )/(2) + 1\\y(t) = (1)/(e^(t ) ) ((t^(2) )/(2) + 1)](https://img.qammunity.org/2021/formulas/mathematics/college/p5ox2dfmjobhwesg3z0nzhwv397prrrseo.png)
The value of y(1) will be expressed as;
![y(1) = (1)/(e^(1) ) ((1^(2) )/(2) + 1)\\y(1) = (1)/(2e)+(1)/(e)\\ y(1) = (3)/(2e)](https://img.qammunity.org/2021/formulas/mathematics/college/gqg8m6fwb7a8kaa84l9zc1wr3fube8y6e1.png)
![y(1) = (3)/(5.4366) \\y(1) = 0.5518](https://img.qammunity.org/2021/formulas/mathematics/college/paetitk9wtwskjwt4pd5a3k4fcqrbqxaks.png)